Santos takes physics-based approach to human motion prediction - Abdel-Malek, Karim (Knovel, 2011)
What do the U.S. Army, Ford Motor Company, and a handful of leading global manufacturers have in common? They are among the pioneers experimenting with a new method for human motion prediction that is the first to incorporate physics. Dubbed Santos, the digital human modeling technology was developed by the research team working on the Virtual Solider Research (VSR) program at the Center for Computer-Aided Design of the University of Iowas College of Engineering. Recognizing an opportunity around the growing demand for digital prototyping and simulation solutions, the team identified limitations of the traditional data-driven approach to human motion prediction, which necessitates thousands of experiments to capture the data for only a few motions.
Keywords: Predictive control.; Robotics.; Artificial intelligence.; Robots.; elektronické knihy; electronic books